Do black women still come first? Examining Essence magazine post Time Warner. Issue 4 (7th August 2016) - Hill, Marcus A.
ABSTRACT: Essence magazine is the longest operating magazine catering to a predominately African-American women audience in the US. In 2000, media conglomerate Time Warner purchased 49% of Essence parent company Essence Communications Inc. In 2005, Time Warner purchased the remaining 51% of the black-owned company. As a media conglomerate, Time Warner owns major publishing houses, film, and television production companies, including 130 magazines, New Line Cinema, CNN, and HBO. Essence states it is "the voice and soul of Black women" Collins [Collins, P. H. (2000). Black feminist thought: Knowledge, consciousness, and the politics of empowerment . New York, NY: Routledge] argues that black women must speak in their own voices in order to reject prevailing stereotypes operating on the bodies of black women. The mission statement of Essence aligns itself in what Collins calls "safe spaces" for black women to self-define themselves and articulate their lived realties. A critical theoretical framework allows uneven power relations to be examined and offers emancipatory perspectives. The goal of this study is to examine if Time Warner's purchase of Essence has caused a shift in the voice and content of this magazine.